Microstructure and wear properties of FeW-SiC based composite coating produced with Tungsten inert gas (TIG) surfacing method - Islak, S.; Eski, O.; Buytoz, S. (Natl Inst Optoelectronics, 2011)
In this study, SiC reinforced and FeW based metal matrix composite (MMC) was produced on substrate of AISI 304 stainless steel using tungsten inert gas (TIG) surfacing process. In order to examine the effect of SiC on microstructure, hardness and abrasive wear properties inside FeW matrix, SiC was changed by ratios of 10, 25, and 50% by weight. Phase compound and microstructure of coating layers were examined using X-ray diffractometer (XRD) and scanning electron microscope (SEM). Wear behaviours of samples were evaluated using pin-on disc sliding wear tests. It was found that Fe2C, Cr7C3, W2C carbide and Fe2Si, CrSi2 silica were formed in the microstructure. The studies conducted concluded that FeW-25 wt.% SiC composite coating was the most appropriate combination in terms of hardness and wear performance.
Keywords: TIG coating; Metal-matrix composite; Microstructure; Wear